2016
DOI: 10.1093/icvts/ivw360
|View full text |Cite
|
Sign up to set email alerts
|

Operative results of the anterolateral thoracotomy with partial sternotomy approach for chronic-type B aortic dissection involving the aortic arch

Abstract: The anterolateral thoracotomy with partial sternotomy approach is a useful surgical procedure with acceptable outcomes for chronic-type B aortic dissection cases involving the aortic arch, when aortic remodelling using thoracic endovascular aortic repair cannot be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Other surgical procedures for an extended thoracic replacement, which can decrease the risk of a future aortic reintervention, were also reported, though these were rarely applied for reoperation after a previous AAAD repair. [6][7][8][9][10][11][12][13] Ishikawa et al and Uchino et al reported ALPS, though their cohort included only 5.5 and 0% of reoperations, respectively. 6,7 Iwasaki et al reported a clamshell approach for an extended thoracic replacement, though there were only 8% of reoperations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other surgical procedures for an extended thoracic replacement, which can decrease the risk of a future aortic reintervention, were also reported, though these were rarely applied for reoperation after a previous AAAD repair. [6][7][8][9][10][11][12][13] Ishikawa et al and Uchino et al reported ALPS, though their cohort included only 5.5 and 0% of reoperations, respectively. 6,7 Iwasaki et al reported a clamshell approach for an extended thoracic replacement, though there were only 8% of reoperations.…”
Section: Discussionmentioning
confidence: 95%
“…[6][7][8][9][10][11][12][13] Ishikawa et al and Uchino et al reported ALPS, though their cohort included only 5.5 and 0% of reoperations, respectively. 6,7 Iwasaki et al reported a clamshell approach for an extended thoracic replacement, though there were only 8% of reoperations. 9 Oishi et al and Tokuda et al reported an L-incision for an extended thoracic replacement, though their cohort included only 2.6 and 10% of reoperations.…”
Section: Discussionmentioning
confidence: 95%
“…Very few reports have been published regarding 1-stage replacement from the aortic arch to thoracoabdominal aorta. 11,18,19 Svensson and colleagues 20 reported a successful case in a 68-year-old patient who underwent replacement of the entire aorta from the aortic valve to the aortic bifurcation via deep hypothermia with circulatory arrest and retrograde perfusion of the brain. Massimo and colleagues 6 reported that 7 patients underwent replacement of the aorta from aortic valve to bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…The anterolateral thoracotomy with partial sternotomy (ALPS), [16][17][18][19] first described by Yunoki and Oba in the 32nd annual meeting of the Japanese Society for Vascular Surgery in 2004, provides sufficient exposure from the aortic valve to the distal descending aorta. In its original form, the lower partial median sternotomy is continued to the anterolateral thoracotomy through the fourth intercostal space.…”
Section: Anterolateral Thoracotomy With Partial Sternotomymentioning
confidence: 99%
“…In its original form, the lower partial median sternotomy is continued to the anterolateral thoracotomy through the fourth intercostal space. 18) This approach provides full access to the aortic root. 17 , 19) To better expose the innominate artery, several authors prefer to enter the third intercostal space.…”
Section: Combined Median Sternotomy and Lateral Thoracotomymentioning
confidence: 99%